A framework for assessing global health impacts of polar change: An urgent call for interdisciplinary research - Netra Naik; Karol Bot; Gail Whiteman; Lora E. Fleming; Karyn Morrissey; Richard Garth James Bellerby; Sam Dupont; Dmitry Yumashev; Susana Hancock; Brendan M. Rogers; Kristie L. Ebi; Joacim Rocklöv (Ambio, 2026)
Research on the human health risks of climate change is expanding, yet the influence of polar region shifts on these risks remains underexplored. This paper presents a framework to assess global and regional health risks stemming from polar physical changes. The polar regions are experiencing rapid environmental transformations, including melting ice, ocean warming, ocean acidification, permafrost thaw, intensifying wildfires, and alterations to jet streams, ocean currents. These changes can amplify global risks, affecting human health even in distant regions. The paper identifies potential cascading impacts on health and well-being via drivers such as extreme weather, heat stress, air, water quality, food supply, safety, vector ecology, and sea-level rise. A scoping review was conducted by an international team of public health and polar experts to support thematic categorization of regional and global health risks. The paper advocates integrating these amplified risks into health impact assessments through interdisciplinary, international collaboration to inform future policy responses.